The reliability, variability and minimal detectable change of multiplanar isometric trunk strength testing using a fixed digital dynamometer - Bucke, J.; Mattiussi, A.; May, K.; Shaw, J. (Journal of Sports Sciences, 2024)
Trunk strength plays a vital role in athletic performance, rehabilitation and general health, however, current assessment methods are expensive, non-portable or unreliable. This study aimed to investigate the within- and between-session reliability, variability, standard error of measurement and minimal detectable change (MDC) of trunk strength in the sagittal (flexion and extension) and frontal planes (left and right lateral flexion) using a fixed digital dynamometer. Eighteen participants (ten men and eight women) attended two sessions separated by 7 days. Participants were fitted with a trunk harness which was secured to an immovable base via a digital dynamometer. Three maximal voluntary isometric contractions were completed across four positions (prone, supine, left-side recumbent and right-side recumbent, respectively) on a glute-hamstring raise machine. All positions demonstrated excellent reliability and low variability within session (ICC: 0.95-0.98; CV: 5-7%) and between sessions (ICC: 0.98-0.99; CV: 4-6%), across all positions. The between-session MDC ranged from 8% (prone) to 13% (right-side recumbent), translating to absolute values between 2.9 and 3.2 kg across all positions. Maximal isometric force testing using a fixed digital dynamometer provides reliable measurements of multiplanar trunk strength, providing a practical method for use in clinical practice.